2019
DOI: 10.18510/hssr.2019.73105
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ethics in Supply Chain Management: Culture as Moderator

Abstract: Purpose: The present study focuses on the role of ethics in the supply chain management. In addition to that the moderating role of culture is also examined. Organizational culture has been regarded as an important determinant of ethical behaviours of managers. This paper assesses the potential of organizational culture to impact ethics in organizations. Methodology: Organizational culture is recognized as one determinant of how people behave, more or less ethically, in organizations. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…However, the review has shown that not only VMI and operational performance in Ghana the adoption of VMI transmutes into OP, but there are also other factors. Jermsittiparsert and Srihirun (2019) suggest that leadership plays an integral role in the success of every organization and its SCM strategies. Implementation, coordination and facilitation of VMI requires top management commitment (Sumrit, 2019) to be effective.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the review has shown that not only VMI and operational performance in Ghana the adoption of VMI transmutes into OP, but there are also other factors. Jermsittiparsert and Srihirun (2019) suggest that leadership plays an integral role in the success of every organization and its SCM strategies. Implementation, coordination and facilitation of VMI requires top management commitment (Sumrit, 2019) to be effective.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Leaders bring improvement and change within an organization which affects organizational performance. The study revealed that the leader of the supply chain brings the improvement and change within the organization (Jermsittiparsert and Srihirun, 2019). Therefore, to achieve high performance, leadership is important.…”
Section: Vmi and Operational Performance In Ghanamentioning
confidence: 99%
“…By ensuring effective, efficient and ethically apt supply chain management functions, profit can increase, goods be delivered on time, waste, administrative cost and legal cost reduced and time maximize. According to Jermsittiparsert and Srihirun (2019), the main purpose of supply chain is supply. While ethical supply is the standard measures put in place to proactively provide supply services and goods to customers.…”
Section: Supply Chain Functionmentioning
confidence: 99%
“…These are the questions that this study is set to answer. Ethics has for long been acknowledged by supporters and admirers from both small and large organisations (Jermsittiparsert and Srihirun, 2019). Ethics prescribed principles that guide humans and guide the way humans conduct at work places and job places and functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to develop a corporate culture, which is constructive and developing, to achieve transition towards sustainability (Kamali & Hewage, 2017). The performance of an organization is made better and the current assets can be used optimally through developing a healthy culture for improvement business performance (Jermsittiparsert & Srihirun, 2019). The performance of the organization is improved in terms of environment, economic and social development (Śmigielska, 2018;.…”
Section: Introductionmentioning
confidence: 99%